2020
DOI: 10.24815/ijdm.v3i1.17298
|View full text |Cite
|
Sign up to set email alerts
|

Development of Knowledge and Attitude Measurement Tools in Disaster Preparedness Schools

Abstract: Indonesia is the largest archipelago country in the world located at the confluence of four tectonic plates. This condition makes Indonesia potentially and become vulnerable to natural hazard that have a significant impact and reach various sectors. One of the impacts of natural hazard that occurred in Indonesia is the education sector. This natural hazard has an impact on the physical building of schools and also hinders the process of teaching and learning, causing trauma, and even fatalities at school. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…Understanding natural calamities refers to the knowledge of different natural disasters. According to Setiawan et al [50], knowledge is an essential factor in disaster management and preparedness for natural calamities. De Coninck et al [51] also found that awareness of the risks and damage that a natural disaster could cause ultimately increase TPB is considered a valuable framework for predicting and identifying an individual's behavior [49].…”
Section: Determinants Of Perceived Severitymentioning
confidence: 99%
“…Understanding natural calamities refers to the knowledge of different natural disasters. According to Setiawan et al [50], knowledge is an essential factor in disaster management and preparedness for natural calamities. De Coninck et al [51] also found that awareness of the risks and damage that a natural disaster could cause ultimately increase TPB is considered a valuable framework for predicting and identifying an individual's behavior [49].…”
Section: Determinants Of Perceived Severitymentioning
confidence: 99%
“…Okada and Matsuda (2006) in their analysis of the participatory process in disaster preparedness argue that disaster preparedness "can hardly be sustained unless appropriate knowledge is shared and transferred among the agents"; in that, people need to gain knowledge on existing hazards and risks, gain know-how on how to survive disasters and gain intrinsic local knowledge through knowledge sharing. Similarly, knowledge, attitude and trust are examined as vital tools for disaster preparedness (Setiawan et al, 2020; Disaster preparedness for foreign residents Uslaner, 2016). Therefore, to understand the success of public engagement activities, some studies rely on the number of participants (either active/passive), level of satisfaction, inclusiveness level and others (Knowlton, 2013).…”
Section: Relevance Of Public Engagement Practices and Approachmentioning
confidence: 99%
“…The role of knowledge in disaster education is the basis or beginning of the actions and awareness of each individual [17,18]. The existence of knowledge capacity can be used as the basis for each individual in taking action before, during, and after a disaster occurs [19,20]. In disaster management, individual or community knowledge is crucial to disaster preparedness [21,22].…”
Section: Implementation In Learning At Schoolmentioning
confidence: 99%
“…The objectives of disaster education in Aceh-Indonesia are as follows [5]. The implementation of education must be adjusted to the characteristics and needs of schools and regions [20]. In practice, schools can collaborate with the government and research institutions at universities nationally and internationally.…”
Section: Implementation In Learning At Schoolmentioning
confidence: 99%